Avaliação de prematuros de muito baixo peso ao nascer no primeiro ano do ambulatório do prematuro da Fundação Santa Casa de Misericórdia do Pará – FSCMPA - MEDEIRO JÚNIOR, Honório Onofre de (2022)
The inquiry was conducted during January-December 2007 to evaluate the growth of children with preterm and weighing less than 1500g at birth, in the first year of the Clinic of the Premature of the FSCMPA; identify possible risk factors related to prematurity and very low birth weight and growth performance of these children. We reviewed 135 medical charts, according to a form that included demographic characteristics of preterm infants and maternal, history of delivery and neonatal and immediate assessment of the growth in age and weight of premature babies. The data obtained were analyzed in a database created in Microsoft programs Excel and EPI-INFO 6.04, with application of chi-square and t-Student. It was observed that among mothers of premature infants, 61.2% were aged below 30 years and of these 21.6% were teenagers (15-19 years), 50.9% underwent cesarean section, 46.6% were predigests, 85.3% had carried through pregnancy care but 56% with number of less than six and 45.7% showed the ITU as the disease urinary-gynecologic more frequent during pregnancy, birth, 53.4% of preterms were male , 93.1% weighed between 1001 to 1500, 73.3% were aged 30.1 to 35 weeks, showed high Apgar scores of the first (median 8.0) and in the fifth minute (Median 9.0) showed similar gain and growth (weight, height and head circumference) progressively lower in the three age groups studied. The results this research show that the mothers of premature infants with very low birth weight, were mostly young, predigests, with carried through pregnancy assistance of inadequate form, with urinary tract infection (UTI) the most frequent urinary-gynecologic disease during pregnancy, boys and girls are also seen in the clinic and about half of those born with very low birth weight, moderately premature infants with high Apgar scores for both the first in the fifth minute, with progressively reduced income in anthropometric measurements related to growth (weight, height and head circumference). Probably, these are characteristics of the mother child factors contributing to prematurity and low birth weight gain of premature infants with reduced growth trend.